261 ANALOG PEPTIDES OF TYPE II COLLAGEN WHICH CAN SUPPRESS ARTHRITIS IN DR4(DRB1*0401) TRANSGENIC MICE. (1st January 2005) - Myers, L. K.; Sakurai, Y.; Brand, D.; Rosloniec, E. F.; Tang, B.; Stuart, J. M.; Kang, A. H.
Abstract : Rheumatoid arthritis (RA) is an autoimmune disease associated with the recognition of self-proteins secluded in peripheral joints. We have previously identified a critical determinant of CII (CII-263-270) that triggers T cell immune responses in HLA-DR4 transgenic mice. In order to produce synthetic peptides with the potential of disrupting the DR4-restricted immune response, synthetic analog peptides were developed that contain site-directed substitutions in critical positions. These analog peptides were used to treat CIA in DR4 Tg mice. In this study, we identify two analog peptides of this immunodominant determinant which can suppress collagen-induced arthritis, CII 256-276 (F263N, E266D), also called A12, and CII 256-270 (F263N, E266A), also called A13. When either peptide is administered to DR4 mice at the time of immunization with CII, arthritis does not develop. Binding studies revealed that substitution of the amino acid (263 phenylalanine) of the CII peptide with an asparagine leads to a significant decrease in the affinity of the peptide to the MHC molecule DR4. On the other hand, substitution of Glu-266 with an alanine caused an increased affinity to the DR4 molecule, while aspartic acid substitution led to a significantly lower (35 fold reduction) in affinity. The modulation of collagen-induced arthritis was associated with an increase in T cell secretion of the Th2 cytokine IL-4 together with a decrease in the Th1 cytokine IFN-γ. These data establish two analog peptides which are potent suppressors of the DR mediated immune response to CII. The effect is mediated, at least in part, by IL-4. These experiments represent the first description of an analog peptide of type II collagen recognized by T cells in the context of the human DR4 molecule that can suppress autoimmune arthritis.